AFM and Cu Electrodeposition Studies of Reduced Graphene Oxide Modified Au(111) Facets Prepared using Electrodeposition and Post-Deposition Pulse Treatment. Issue 9 (16th September 2021) - Liu, Zhiguang; Jan Grzędowski, Adrian; Guo, Yujing; Bizzotto, Dan
Abstract : The structural and electrochemical characteristics of electrodeposited graphene oxide (GO) onto a single crystal gold bead electrode was studied using AFM and Cu electrodeposition. Optimal deposition uniformity was realized by rotation of the electrode, suggesting an initial electrophoretic deposition occurs followed by some reduction of the GO. Potential pulse treatments to reducing potentials for a short time significantly improve the electrochemical characteristics of the electrochemical reduced graphene oxide (ERGO). Both under-potential and over-potential Cu electrodeposition was used to characterize the quality of the ERGO deposit and showed that the gold surface was completely coated with ERGO only after potential pulsing treatments. AFM analysis of ERGO modified Au(111) facet on the gold bead electrode revealed the deposition was composed of sheets of GO/ERGO as well as much rougher deposits. AFM showed that the potential pulsing treatment resulted in the nucleation and growth of electrodeposited Cu nanoparticles over much of the ERGO surface, in contrast to the limited deposition of nanoparticles on the untreated GO deposit. The ERGO modified gold surface prepared using electrodeposition followed by potential pulse treatments results in conductive and electrochemically active ERGO surfaces.